Disambiguating Databases. - RICHARDSON, RICK (Communications of the ACM, 2015)
The article explains the functions and operations of databases so as to aid those managing data storage in selecting the most appropriate one. It outlines the three types of data models in databases, relational, key-value, and hierarchical; different types of application programming interfaces (APIs); and the steps of a database transaction. It assesses different kinds of databases with respect to criteria including speed and data protection. Topics include the limitations of hard disks versus solid-state drives (SSDs), the benefits of SQL versus non-SQL databases, the role of page caches, and indexing.